METODE-METODE YANG KREATIF DAN EFEKTIF UNTUK PENCAPAIAN TUJUAN PENDIDIKAN AGAMA KRISTEN - Tubagus, Steven (Tumou Tou, 2019)
Creative and effective methods for achieving the goals of Christian education. The aim of learning is not just to master concepts knowledge and be skilled in motor skills, but to change attitudes. The method used is qualitative, using the study of literature that is the Bible and reference books. Both school and outside school students have a good signal and people of students are satisfied with the character changes that occur in students, so the methods used are very effective. Methods should not be the main thing by ignoring teaching. The method is used to support teaching so that educational goals are achieved. The various methods will help students to understand the teaching material delivered. The teaching-learning process must be done by various methods. Teachers must have the ability to teach both cognitively, psychomorically, and affective to achieve the goals of Christian religious education. Hold everything that you have heard from me as an example of sound teaching and do it in faith and love in Christ Jesus.